2017
DOI: 10.1177/1708538117721622
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned return to operating room after endovascular repair of abdominal aortic aneurysm (EVAR) is associated with increased risk of hospital readmission

Abstract: Objectives Hospital readmissions after surgical operations are considered serious events. Centers for Medicare and Medicaid (CMS) consider surgical readmissions as preventable and hold hospitals responsible for them. Endovascular abdominal aortic aneurysm (EVAR) has become the first line modality of treatment for suitable patients with abdominal aortic aneurysm (AAA). The purpose of this study is to retrospectively review the factors associated with hospital readmission after EVAR. Methods The 2013 EVAR target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“… 27 Residual aortic disease, complications with grafts, and preexisting cardiovascular comorbidities were found to be the main drivers of readmission after TBAD repair. Additionally, Aziz and colleagues 14 showed that the most common cause of readmission after the endovascular repair of abdominal aortic aneurysm was infection, including superficial and deep surgical site infection. As the third most common reason for readmission in our overall cohort, infection is a preventable complication that should be addressed through targeted strategies to reduce readmission and associated costs during the first postoperative year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Residual aortic disease, complications with grafts, and preexisting cardiovascular comorbidities were found to be the main drivers of readmission after TBAD repair. Additionally, Aziz and colleagues 14 showed that the most common cause of readmission after the endovascular repair of abdominal aortic aneurysm was infection, including superficial and deep surgical site infection. As the third most common reason for readmission in our overall cohort, infection is a preventable complication that should be addressed through targeted strategies to reduce readmission and associated costs during the first postoperative year.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Independent predictors of readmission have been identified across numerous aortic surgical procedures, including abdominal aortic aneurysm repair and Stanford Type A aortic dissection. 13 , 14 Although several studies have investigated outcomes and short-term readmission rates after aortic dissection repair, 15 , 16 risk factors that lead to readmission during the first postoperative year remain unknown. Using a large nationwide database, we analyzed the features of patients with TBAD who undergo TEVAR or OSR and determined the rates and risk factors of readmission during the first postoperative year.…”
mentioning
confidence: 99%
“…This database has been previously utilised in orthopaedic and other surgical publications. 8,19,20 Institutional Review Board deemed this study exempt as the data analysed is from a public source.…”
Section: Data Sourcementioning
confidence: 99%